Public Communication and Fake News: Combating Misinformation in the Post-Truth Era - Diah Fatma Sjoraida; Bucky Wibawa Karya Guna; Aat Ruchiat Nungraha; Yatimin (AKADEMI TEKNIK ADI KARYA, 2025)
In the post-truth era, where emotions and personal beliefs often override objective facts, the spread of fake news poses significant challenges to public communication. This study examines the role of public communication in identifying, addressing, and combating misinformation across digital platforms. Through a qualitative content analysis of government campaigns, media initiatives, and public responses, this research highlights the strategies employed to mitigate the impact of fake news on public opinion and democratic discourse. The findings indicate that transparency, media literacy, fact-checking mechanisms, and real-time engagement are critical components of effective public communication. Furthermore, the study underscores the need for cross-sector collaboration among governments, media organizations, and civil society to build public resilience against misinformation. This research contributes to the growing body of literature on digital communication and offers practical recommendations for policymakers and communication professionals navigating the complexities of the post-truth information landscape.